Moku Hesi Miti Tradition: Birth Ritual in Ethnoparenting of Takpala Indigenous Village Community, Alor Regency - Wollo, Stevanya Lucia Wety; Rachmawati, Yeni; Syaodih, Ernawulan (Yayasan Keluarga Guru Mandiri, 2026)
This study examines “Moku Hesi Miti,